Pharmacognistic, proximate and phytochemical analysis of stem of Cistanche tubulosa (Schenck) Hook. F.: Analysis of C. tubulosa properties - Nousheen , Maryum; Basit , Abdul; Kamran Khan , Muhammad; Alzayed, Rasha M.; Alhajouj, Sondos A.; Alaida, Meaad F.; Omran, Awatif M. E; Alasmari, Abdulrahman; El Askary, Ahmad; Almalki, Riyadh S.; Zayed, Mohamed M. (Cellular and Molecular Biology, 2025)
A medicinal plant is any plant that in one or more of its organs contains substances that can be used by it or their constituent for therapeutic purposes. The present work was done to evaluate pharmacognostic, fluorescence, proximate and phytochemical analysis of ethanolic extracts of Cistanche tubulosa (Orobanchaceae) along with antimicrobial activity. Antimicrobial activity against four bacterial strains S. aureus, E. coli, P. aeruginosa, S. typhi along with five fungal strains such as F. oxyfurum, P. notatum, Candida albicans, A. fumigatus, and A. niger evaluate using agar well diffusion method. The powder drug study of various tissues of plants revealed higher concentrations (20.29 mg/l) of essential macro and micronutrients. Fluorescence analysis of the stem powdered with various chemical reagents showed different colors. Proximate analysis showed the presence of crude substances such as proteins (8.5 %), fat (1.5 %), fibres (6.6 %), carbohydrates (73.87 %), moisture contents (3.23 %) and ash contents (6.3 %) respectively. Phytochemical screening revealed the presence of carbohydrates, proteins and dozen other important secondary metabolites. The presence of these bioactive constituents associated with the antimicrobial activity of S. aureus showed the maximum zone of inhibition (15.1 ± 3.7 mm), while in antifungal activity C. albicans showed the highest zone of inhibition (11.0 ± 3.15 mm). The pharmacognostic study, fluorescence analysis and antimicrobial activity are helpful in the standardization of the drug establishing a good support for the use of C. tubulosa in traditional medicine.